Pengaruh Return On Assets, Return On Equity, Earning Per Share, Dan Debt To Equity Ratio Terhadap Harga Saham - Ikhda Choeru Tunisa; Agus Endro Suwarno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to determine the influence of Return On Assets, Return On Equity, Earning Per Share, and Debt To Equity Ratio on stock prices in companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sampling method employed in this research is purposive sampling technique, resulting in a sample size of 111 companies over 3 years. Secondary data was utilized and processed using SPSS. The findings of the research indicate that Return On Assets has no significant effect on stock prices, Return On Equity has no significant effect on stock prices, Earning Per Share has a significant effect on stock prices, and Debt To Equity Ratio has no significant effect on stock prices.